Plan estratégico de marketing para la empresa Café Indera de la ciudad de Loja, 2023. - Campoverde Elizalde, Natali Silvana (2024)
The main objective of this research is to develop a strategic marketing plan for the company “Café Indera” in Loja city, in order to optimize its activities and strengthen its position in the market. In the internal analysis, the EFI matrix was constructed through the information obtained from the interview, the surveys and the direct observation form, where a weighted value of 2.90 was obtained, which indicates that the company has a strong position; this information also allowed determining the preferences of consumers related to the company's marketing. In the external analysis, a PESTE analysis was performed, which allowed determining the impact of political, economic, social, technological and ecological factors, in addition to the study of Porter's forces, which allowed having a more general overview of the company, such information is reflected in the EFE matrix, obtaining a weighted value of 2.55, which indicates that the opportunities predominate over the threats, the company is slightly above the established measure, with such information the swot matrix is made. Based on the results, we proceeded to establish the strategies for the proposal of the strategic marketing plan. Three strategic objectives were proposed, based on developing a redesign of the company's institutional image, implementing a promotion and training plan with its corresponding action plan. The total budget for the strategic marketing plan is $1,267.00. Once the research was completed, the respective conclusions and recommendations necessary for the company to achieve its objectives and better position itself in the market were established.